EFFECT OF FIRM SIZE AND CAPITAL STRUCTURE ON FIRM VALUE WITH PROFITABILITY AS AN INTERVENING VARIABLE IN MANUFACTURING COMPANIES - Silvia Sari; Lusiana -; Zefriyenni - (Jurnal Ipteks Terapan, 2023)
The purpose of this study is to examine the effect of firm size and capital structure on firm value, profitability being an intermediate variable. The sampling method used purposeful sampling, with samples of hilir kuantitas from 60 manufacturing companies listed on the Indonesian Stock Exchange. The analytical methods used are classical hypothesis and multiple linear regression analysis. The results show that firm size has a partial effect on profitability, capital structure has a partial effect on profitability, and firm size has a partial influence on firm value. company, partial profits significantly affect the value of the company. , profitability mediated and unmediated firm size and partial capital structure have a significant effect on firm value, profitability without intermediate variables. R2 (R squared) adjusted is 0.406 or 40.6%, which indicates that the contribution of the variables of firm size, capital structure and profitability to the firm value variable is 40 .6%, while the remaining 59.4% is affected by other external factors. variable. this study such as the financial performance of poros, diversity of the board and other issues.